Quality, Quantity and Duration of Lives - Jean-Yves Duclos; Bouba Housseini (Fondation pour les études et recherches sur le développement international (FERDI), 2015)
The evaluation of development processes and of public policies often involves comparisons of social states that differ in income distributions, population sizes and life longevity. This may require social evaluation principles to be sensitive to the quality, the quantity and the duration of lives. This paper 1) reviews some of the normative issues at stake, 2) proposes and discusses some specific methods to address them in a generalized utilitarian framework, and 3) briefly illustrates the application of some of these methods to the global distribution of incomes, population sizes and longevity over the last century. Depending on the approach taken, it is found inter alia that global social welfare in 2010 can be deemed to be between 1.8 and 407 times that of 1910, the role given to the quantity of lives being particularly important in that assessment.
Keywords: I31; J17; 330